Issues of the history of the Early Hittite Kingdom - Ghazaryan, Robert (Bulletin of the institute of oriental studies (Online), 2023)
The Hittite state is closely related to the kingdom of Kanesh by historical ties. Its background could be understood through the study of the last stage of the history of the citystate Kanesh or Nesa in the second half of the II millennium BC. It is also essential to understand how the transition of the state system from Kanesh to Hattusa took place. It is equally necessary to find the connection between the kings of the Old Hittite Kingdom and the Kanesh dynasty and the influence that the state system of Kanesh had on the Old Hittite state. The article discusses the above-mentioned issues, as well as a number of other issues of the history of the Early Hittite state. Խեթական պետությունը պատմական կապերով սերտորեն առնչվում է Քանեշի թագավորության հետ։ Նրա նախապատմությունը վեր հանելու համար, հարկավոր է ուսումնասիրության առարկա դարձնել մ.թ.ա. II հազարամյակի II կեսի Քանեշ կամ Նեսա քաղաք-պետության պատմության վերջին փուլը։ Կարևոր է նաև հասկանալ, թե ինչպես է տեղի ունեցել պետական համակարգի անցումը Քանեշից դեպի Խաթթուսա: Հարկավոր է նաև պարզել կապը խեթական Հին թագավորության արքաների և քանեշյան արքայատոհմի միջև և այն, թե ինչ ազդեցություն է թողել Քանեշի պետական համակարգը Հին խեթական պետության վրա։ Հոդվածում քննարկման առարկա են դարձել վերոհիշյալ խնդիրները, ինչպես նաև Վաղ խեթական պետության պատմության մի շարք այլ հիմնախնդիրներ։